2020
DOI: 10.1155/2020/9136256
|View full text |Cite
|
Sign up to set email alerts
|

Management Outcome of Burn Injury and Associated Factors among Hospitalized Children at Ayder Referral Hospital, Tigray, Ethiopia

Abstract: Background. Burn injuries are a global public health problem, accounting for an estimated 265,000 deaths. Globally, over half of the disability-adjusted life years lost from fire-related burns which occurred between the ages of 0 and 14 years. The rate of child deaths from burns is currently over 7 times higher in low- and middle-income countries than in high-income countries. In Ethiopia, burn was the second leading cause of death among children from the unintentional injuries. So far, no research had been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 16 publications
8
28
3
Order By: Relevance
“…About 41.0% of the burn patients were presented lately after 24 hours of burn. 18 A study reported 10% of epileptic patients sustained burns as a result of seizures. 19 A study by Mengistu et al reported among patients who felt severe pain (87.1%), most of them (48.4%) took paracetamol, 30.6% took tramadol, and the remaining 8.1% took nonsteroidal anti-inflammatory drugs (diclofenac).…”
Section: Introductionmentioning
confidence: 99%
“…About 41.0% of the burn patients were presented lately after 24 hours of burn. 18 A study reported 10% of epileptic patients sustained burns as a result of seizures. 19 A study by Mengistu et al reported among patients who felt severe pain (87.1%), most of them (48.4%) took paracetamol, 30.6% took tramadol, and the remaining 8.1% took nonsteroidal anti-inflammatory drugs (diclofenac).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the total complication is in line with the study conducted in Bahir Dar. 10 However, the finding is higher than the study conducted in Addis Ababa, 21 Mekelle, 9 and America. 8 The reason for the discrepancy is due to the study conducted in Addis Ababa and Mekelle were conducted in specialized referral hospitals, which have better facilities to manage burn injury than our study setting, which is a district hospital with a poor facility to manage burn injury.…”
Section: Discussionmentioning
confidence: 78%
“…The authors prepared the checklist by reviewing different literature done on the same problems. [8][9][10][16][17][18][19] The checklist was focused on socio-demographic characteristics of an injured child, burn-related factors, treatment-related factors, and outcome-related factors. Eight trained BSc nurses who were working on the site other than the study setting were involved in the data collection and were supervised by four physicians who were also not a member of the study setting.…”
Section: Data Collection Tools and Methodsmentioning
confidence: 99%
See 2 more Smart Citations